Can silicon carbide serve as a saturable absorber for passive mode-locked fiber lasers? - Cheng, Chih-Hsien (Sci Rep, 2015)
The study presents a novel demonstration of a passively mode-locked erbium-doped fiber laser (EDFL) that is based on a silicon carbide (Si(x)C(1−x)) saturable absorber. When the C/Si composition ratio is increased to 1.83, the Si(x)C(1−x) film transforms from two-photon absorption to nonlinear saturable absorption, and the corresponding value reaches −3.9 × 10(−6) cm/W. The Si-rich Si(x)C(1−x) film cannot mode lock the EDFL because it induced high intracavity loss through two-photon absorption. Even when a stoichiometric SiC is used, the EDFL is mode locked, similar to an EDFL operating under weak nonlinear-polarization-rotation condition. A C-rich Si(x)C(1−x) film containing sp(2)-orbital C–C bonds with a linear absorbance of 0.172 and nonlinear absorbance of 0.04 at a 181 MW/cm(2) saturation intensity demonstrates nonlinear transmittance. The C-rich Si(x)C(1−x) saturable absorber successfully generates a short mode-locked EDFL pulse of 470 fs. The fluctuation of the pulse-train envelope dropps considerably from 11.6% to 0.8% when a strong saturable-absorption-induced self-amplitude modulation process occurs in the C-rich Si(x)C(1−x) film.